Ralph Waldo Emerson papers - Emerson, Ralph Waldo, 1803-1882.
Correspondence, newspaper clippings, and other papers. Correspondents include William Jennings Bryan, Thomas Carlyle, Eliza Thayer Clapp, W.C. Forster, and William Herbert Withington.
Author and poet.
Collection material in English.
Keywords: Bryan, William Jennings, -- 1860-1925 -- Correspondence; Carlyle, Thomas, -- 1795-1881 -- Correspondence; Clapp, Eliza Thayer, -- 1811-1888 -- Correspondence; Forster, W. C. -- Correspondence; Withington, William Herbert, -- 1835-1903 -- Correspondence; Authors; Poets